Trinidad, North Coast - (:unkn) unknown (Davidson and Todd Ltd., Trinidad., 2009)
A painting of the ocean on Trinidad's North coast through the trees from a hilltop.
Colour; Coloured; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Coasts